Pronunciation instruction in digital EFL programs at Indonesian university: Pedagogical challenges and opportunities - Yuliyanto Sabat; Abd. Syakur; Lailatul Musyarofah (Universitas Muhammadiyah Malang, 2026)
The use of digital technology has significantly transformed traditional pedagogical practice for pronunciation instruction. Numerous studies have explored the positive and negative impact of digital tools in pronunciation instruction, yet only a limited number of studies emphasize the pedagogical challenges and opportunities of digital devices in pronunciation instruction, particularly within Indonesian higher education level. To fill this gap, this qualitative study investigates the pedagogical challenges and opportunities of pronunciation instruction in digital EFL programs at Indonesian university. Data collection was conducted through semi-structured interviews and class observations involving 29 participants, including 2 EFL lecturers and 27 university students. Findings reveal that while digital platforms such as mobile apps, websites, YouTube, LMS, and AI-powered platforms facilitate increased learner autonomy and provide authentic pronunciation models, barriers persist in the form of limited digital literacy among lecturers, inadequate institutional support, and infrastructural constraints. Despite these challenges, lecturers and students generally hold positive attitudes toward technology integration, recognizing its potential to enhance the process of pronunciation teaching and learning. The study underscores the need for targeted professional development and greater institutional investment to fully leverage digital technologies in pronunciation instruction. Implications for policy and pedagogy in similar developing contexts are discussed.